The Outcomes of Patients With Neck Pain Following ACDF: A Comparison of Patients With Radiculopathy, Myelopathy, or Mixed Symptomatology. Issue 21 (1st November 2020) - Stull, Justin D.; Goyal, Dhruv K. C.; Mangan, John J.; Divi, Srikanth N.; McKenzie, James C.; Casper, David S.; Okroj, Kamil; Kepler, Christopher K.; Vaccaro, Alexander R.; Schroeder, Gregory D.; Hilibrand, Alan S.
Abstract : Study Design: Retrospective cohort study. Objective: The goal of the present study was to determine whether neck pain responds differently to anterior cervical discectomy and fusion (ACDF) between patients with cervical radiculopathy and/or cervical myelopathy. Summary of Background Data: Many patients who undergo ACDF because of radiculopathy/myelopathy also complain of neck pain. However, no studies have compared the response of significant neck pain to ACDF. Methods: Patients undergoing one to three-level primary ACDF for radiculopathy and/or myelopathy with significant (Visual Analogue Scale [VAS] ≥ 3) neck pain and a minimum of 1-year follow-up were included. Based on preoperative symptoms patients were split into groups for analysis: radiculopathy (R group), myelopathy (M group), or both (MR group). Groups were compared for differences in Health Related Quality of Life outcomes: Physical Component Score-12, Mental Component Score (MCS)-12, Neck Disability Index, VAS neck, and VAS arm pain. Results: Two hundred thirty-five patients met inclusion criteria. There were 117 patients in the R group, 53 in the M group, and 65 in the MR group. Preoperative VAS neck pain was found to be significantly higher in the R group versus M group (6.5 vs. 5.5; P = 0.046). Postoperatively, all cohorts experienced significant ( P < 0.001) reduction in VAS neck pain, (ΔVAS neck; R group: −2.9, M: −2.5, MR: −2.5) with no significant differences between groups. However, myelopathic patients showed greater improvement in absolute MCS-12 scores ( P = 0.011), RR ( P = 0.006), and % minimum clinically important difference ( P = 0.013) when compared with radiculopathy patients. This greater improvement remained following regression analysis ( P = 0.025). Conclusion: Patients with substantial preoperative neck pain experienced significant reduction in their neck pain, disability, and physical function following ACDF, whether treated for radiculopathy or myelopathy. However, in this study, only myelopathy patients had significant improvements in their mental function as represented by MCS improvements. Level of Evidence: 3 Abstract : A retrospective analysis of prospective data was performed to compare HRQOL outcomes between radiculopathic and myelopathic patients with substantial preoperative neck pain undergoing ACDF. There was statistically significant improvement in neck pain for each cohort. In addition, myelopathic patients had greater MCS-12 improvement than the radiculopathy group.